2018
DOI: 10.1177/0961203317751851
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nutritional intervention on the lipid profile and dietary intake of adolescents with juvenile systemic lupus erythematosus: a randomized, controlled trial

Abstract: Objective This study sought to evaluate the effects of a nutritional intervention on the lipid metabolism biomarkers associated with cardiovascular risk, and their variation over time, in juvenile systemic lupus erythematosus (JSLE) patients. This study also investigated the relationships between these biomarkers and dietary intake, nutritional status, disease variables, and medication used. Methods A total of 31 10- to 19-year-old female adolescents with JSLE for at least six months were analyzed. The partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…Our group has previously reported a high prevalence of dyslipidemia in children and adolescents with JIA and jSLE. [6][7][8][9] It is well established in the literature that dyslipidemia is a relevant factor for triggering the atherosclerotic process. 1 To our knowledge, this is the first study conducted in the pediatric population that describes the prevalence of dyslipidemia in individuals with JDM.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has previously reported a high prevalence of dyslipidemia in children and adolescents with JIA and jSLE. [6][7][8][9] It is well established in the literature that dyslipidemia is a relevant factor for triggering the atherosclerotic process. 1 To our knowledge, this is the first study conducted in the pediatric population that describes the prevalence of dyslipidemia in individuals with JDM.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the use of medication, in the studies by Davies et al [7] and Silva et al [11], there was no significant difference between the groups in terms of prednisolone dosage and hydroxychloroquine users. Shah et al [8] found that prednisolone use was slightly higher in the control group but without significant difference.…”
Section: Medication Used By Patientsmentioning
confidence: 89%
“…Silva et al [11]. included adolescents diagnosed with systemic lupus erythematosus for at least six months, with any clinical manifestation and disease activity.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Other patient groups responding well to treatment with statins, as assessed by HDL and LDL-C levels, have been shown to have high ApoB[47, 48]; thus apolipoprotein measures could help optimise the efficacy of lipid modifying therapy by targeting the correct patients. In addition to statins other interventions could also be relevant including PCSK9 inhibitor[49] and nutritional intervention through increased dietary intake of omega-3 FAs[50, 51]. The efficacy of personalised nutritional therapy has been validated recently in patients with diabetes; high variability between post-meal glucose levels in patients was used to stratify patients for specific short-term personalised dietary interventions to manage glucose levels[52].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of personalised nutritional therapy has been validated recently in patients with diabetes; high variability between post-meal glucose levels in patients was used to stratify patients for specific short-term personalised dietary interventions to manage glucose levels[52]. Dietary intervention has been shown to reduce disease activity scores in SLE patients[50, 53] and patients are very engaged with such strategies[25].…”
Section: Discussionmentioning
confidence: 99%